The Western diet puzzle: connecting metabolic dysfunction to cognitive and neurological consequences - Ibeh, Stanley; Babale, Ismail; Nwaiwu, Judith; Reslan, Mohammad; Mohamed, Wael Mohamed Yousef; Goli, Mona; Mechref, Yehia; Kobeissy, Firas (Springer, 2024)
There has been a significant rise in the consumption of Western diet (WD), which are diets composed of high levels of processed sugar and saturated fat. This unhealthy eating habit has been linked to the development of several chronic diseases, such as obesity, diabetes mellitus, metabolic syndrome, and cardiovascular diseases. Although the effect of WD on metabolic and cardiovascular impairment has received significant attention, how it influences brain function, both in normal and pathologic states is just beginning to gain recent interest. WD has been linked to the alteration of cognitive and neurological function, which is a phenotype that is observed in several neurological disorders such as Alzheimer’s disease, Parkinson’s disease, and traumatic brain injury. The underlying mechanism through which WD induces this effect involves the alteration of cellular homeostasis in the brain microenvironment, which triggers neuroinflammation and the activation of glial cells. Additionally, energy metabolism within the brain is disrupted, leading to the uncoupling of the mitochondria, increased release of ROS, and oxidative stress. Since synaptic plasticity is an energy-intensive process, the distortion of metabolism significantly impacts synaptic plasticity, which potentially leads to altered learning and memory processes and cognitive dysfunction. Also, WD alters the expression of key synaptic proteins that are involved in cognition. This book chapter highlights the cellular and molecular mechanism, through which WD impacts brain function. Also, it details how WD influences the pathologies of several neurological disorders and can lead to worsened functional outcomes.